Imaging of Virus-Infected Cells with Soft X-ray Tomography - Damià Garriga (MDPI AG, 2021)
Viruses are obligate parasites that depend on a host cell for replication and survival. Consequently, to fully understand the viral processes involved in infection and replication, it is fundamental to study them in the cellular context. Often, viral infections induce significant changes in the subcellular organization of the host cell due to the formation of viral factories, alteration of cell cytoskeleton and/or budding of newly formed particles. Accurate 3D mapping of organelle reorganization in infected cells can thus provide valuable information for both basic virus research and antiviral drug development. Among the available techniques for 3D cell imaging, cryo–soft X-ray tomography stands out for its large depth of view (allowing for 10 µm thick biological samples to be imaged without further thinning), its resolution (about 50 nm for tomographies, sufficient to detect viral particles), the minimal requirements for sample manipulation (can be used on frozen, unfixed and unstained whole cells) and the potential to be combined with other techniques (i.e., correlative fluorescence microscopy). In this review we describe the fundamentals of cryo–soft X-ray tomography, its sample requirements, its advantages and its limitations. To highlight the potential of this technique, examples of virus research performed at BL09-MISTRAL beamline in ALBA synchrotron are also presented.